Intelligence and Security Informatics Pacific Asia Workshop, PAISI 2009, Bangkok, Thailand, April 27, 2009. Proceedings - Chen, Hsinchun; Yang, Christopher C.; Chau, Michael; Li, Shu-Hsing.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the refereed proceedings of the Pacific Asia Workshop on Intelligence and Security Informatics, PAISI 2009, held in Bangkok, Thailand, in April 2009. The 10 revised full papers, 7 revised short papers together with 1 keynote lecture were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on terrorism informatics and crime analysis enterprise risk management emergency response and surveillance information access and security, as well as data and text mining.
Keynote -- Building a Geosocial Semantic Web for Military Stabilization and Reconstruction Operations -- Terrorism Informatics and Crime Analysis -- Criminal Cross Correlation Mining and Visualization -- A Cybercrime Forensic Method for Chinese Web Information Authorship Analysis -- Prediction of Unsolved Terrorist Attacks Using Group Detection Algorithms -- Enterprise Risk Management -- Exploring Fraudulent Financial Reporting with GHSOM -- Identifying Firm-Specific Risk Statements in News Articles -- Predicting Future Earnings Change Using Numeric and Textual Information in Financial Reports -- Emergency Response and Surveillance -- When Generalized Voronoi Diagrams Meet GeoWeb for Emergency Management -- E3TP: A Novel Trajectory Prediction Algorithm in Moving Objects Databases -- Information Access and Security -- A User-Centered Framework for Adaptive Fingerprint Identification -- Design of a Passport Anti-forgery System Based on Digital Signature Schemes -- A Chronological Evaluation of Unknown Malcode Detection -- Data and Text Mining -- Relation Discovery from Thai News Articles Using Association Rule Mining -- Discovering Compatible Top-K Theme Patterns from Text Based on Users$1 (BPreferences -- Juicer: Scalable Extraction for Thread Meta-information of Web Forum -- A Feature-Based Approach for Relation Extraction from Thai News Documents -- An Incremental-Learning Method for Supervised Anomaly Detection by Cascading Service Classifier and ITI Decision Tree Methods -- Quantifying News Reports to Proxy (3z(BOther Information(3y (Bin ERC Models.s
Keywords: Computer science; Computer communication systems; Computer security; Data mining; Computers and civilization; Computers; Law and legislation; Computer Science; Systems and Data Security; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Computer Communication Networks; Computers and Society; Legal Aspects of Computing; Electronic books